Operationalizing regional One Health initiatives in Southeast Asia: Ways forward - Lam, Steven; Sinh Dang-Xuan; Unger, Fred; Meeyam, T.; Phuc Pham-Duc; Wacharapluesadee, S.; Hung Nguyen-Viet (Elsevier, 2025)
Operationalizing One Health initiatives that link human, animal, and environmental health at the regional level is key for jointly addressing infectious diseases that can cross borders. This work is urgently needed in Southeast Asia, a recognized hotspot for emerging animal and human infectious diseases that have the potential to spread globally. As such, our objective is to identify action items to advance regional One Health efforts in Southeast Asia. We organized a 1.5-day workshop that convened 34 experts from government, national research institutes, universities, and international organizations spanning seven countries in Southeast Asia. Group discussions and prioritization exercises were conducted which led to 12 action items, serving as ideas for resourcing, operationalizing, and implementing One Health efforts in Southeast Asia. Participants also emphasized the importance of sustained funding, a collective voice, and a willingness among members to be bold in their collective efforts. Given the heightened focus on zoonotic risks in Southeast Asia, harnessing this momentum by operationalizing regional efforts could establish a solid foundation to draw on when facing future global health threats.